2010
DOI: 10.1016/j.aller.2010.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Drug provocation tests to betalactam antibiotics: experience in a paediatric setting

Abstract: Background: Few studies have been performed in children with suspected betalactam allergy. We aimed to assess the role of the drug provocation test (DPT) with betalactams in a paediatric setting and to study the association between allergy to betalactam antibiotics and other allergic diseases. Methods: We included all the patients under 15 years old who were consecutively referred to the Immunoallergy Department, Dona Estefânia Hospital, Portugal (January 2002 to April 2008) for a compatible history of allergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 35 publications
3
35
0
1
Order By: Relevance
“…In our study, clinical symptoms indicating positive DPTs included skin rash in 11 of 16 (68%) patients, angioedema in 2 (18%), and pruritus in 2 (18%). In addition, dizziness, anaphylaxis, dyspnea, and abdominal pain accompanied by vomiting occurred in 1 each, and these results are similar patterns to other studies7,13). Because drug allergies may involve organs other than the skin and skin lesions may appear in various patterns, the presence of a skin lesion per se is not helpful in diagnosing the allergy or determining its method of treatment17).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In our study, clinical symptoms indicating positive DPTs included skin rash in 11 of 16 (68%) patients, angioedema in 2 (18%), and pruritus in 2 (18%). In addition, dizziness, anaphylaxis, dyspnea, and abdominal pain accompanied by vomiting occurred in 1 each, and these results are similar patterns to other studies7,13). Because drug allergies may involve organs other than the skin and skin lesions may appear in various patterns, the presence of a skin lesion per se is not helpful in diagnosing the allergy or determining its method of treatment17).…”
Section: Discussionsupporting
confidence: 75%
“…According to the individual DPTs, there were 17 (23.9%) positive DPTs in 71 events of DPTs. In this study the positive rate of DPTs are relatively higher than those of other studies7,13). In one retrospective study performed in children and adult ADRs, they confirmed that 241 (17.6%) of 1,372 patients were positive on the drug provocation test7).…”
Section: Discussionsupporting
confidence: 74%
“…Three studies highlighted that anaphylaxis, urticaria and angio-oedema index responses were associated with a higher likelihood of positive DPT or ID responses when compared with non-specific rashes, however did not preclude investigation 24 34–36. One study suggested that food allergy was a risk factor for β-lactam allergy among 161 Portuguese children (p=0.047) 37. Kidon and See38 found that having asthma predisposed towards failing drug DPTs, however was unable to correct for their increased medication requirement.…”
Section: Resultsmentioning
confidence: 99%
“…Among children, a recent study [22] regarding nonimmediate reaction to cephalosporin has demonstrated similar results, with low reproducibility of the reaction (two out of 105; 2%), one detected by positive response to skin tests, and another by positive DPT. In particular situations with noncooperative young children (only 47 out of 161; 29% of children accepted skin testing in one study), DPT without previous skin testing was considered a relatively well tolerated procedure in children with a history of mild cutaneous eruption to b-lactams [29]. However, further studies in large numbers of patients and in different age groups are required before the safety of this approach can be established.…”
Section: Key Pointsmentioning
confidence: 99%